2002
DOI: 10.1200/jco.2002.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microvessel Density as a Predictor of Recurrence After Resection of Hepatocellular Carcinoma: A Prospective Study

Abstract: This study shows that a high MVD-CD34 was predictive of early postresection recurrence in patients with HCCs < or = 5 cm and, therefore, may be a novel prognostic marker in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
212
3
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(226 citation statements)
references
References 44 publications
4
212
3
7
Order By: Relevance
“…[48][49][50] In HCC, several groups have reported that high tumor MVD by CD34 or vWF immunostaining may serve as an adverse prognostic marker for HCC less than 5 cm. 51,52 Some suggested that higher tumor MVD may predispose to micrometastasis and tumor angiogenesis may be one of the most important factors to influence tumor recurrence of small HCC. Therefore, it would be interesting to assess whether the MVD measured with the novel markers reported in the current study may prove to be a better and more reliable prognostic marker than CD34.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] In HCC, several groups have reported that high tumor MVD by CD34 or vWF immunostaining may serve as an adverse prognostic marker for HCC less than 5 cm. 51,52 Some suggested that higher tumor MVD may predispose to micrometastasis and tumor angiogenesis may be one of the most important factors to influence tumor recurrence of small HCC. Therefore, it would be interesting to assess whether the MVD measured with the novel markers reported in the current study may prove to be a better and more reliable prognostic marker than CD34.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CD151 or a high MVD alone was correlated with a poor prognosis for HCC patients. 6,27 To evaluate the prognostic significance of the overexpression profile of CD151, MMP9, and MVD together, immunohistochemical double-staining analysis of CD151, MMP9 expression, and MVD-CD34 staining was performed. Simultaneously higher levels of CD151, MMP9 expression, and MVD were observed in HCC tissues with a malignant phenotype (e.g., microvascular invasion, larger size, and dedifferentiation; Supporting Information Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…6 The MVD was evaluated as described elsewhere. 27 Statistical Analysis. Statistical analysis was performed with SPSS12.0 software (SPSS, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
“…The preoperative clinical diagnosis of HCC met the diagnostic criteria of the American Association for the Study of Liver Diseases (Bruix and Sherman, 2005;Bridges et al, 2011 (Poon et al, 2002), (c) complete clinicopathologic and follow-up data. The exclusion criteria included (a) extra hepatic spread and (b) prior anticancer treatments before liver resection.…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%